2014
DOI: 10.1016/j.bbrc.2013.11.071
|View full text |Cite
|
Sign up to set email alerts
|

CB2 cannabinoid receptor is a novel target for third-generation selective estrogen receptor modulators bazedoxifene and lasofoxifene

Abstract: The purpose of the current study was to investigate the ability of the third-generation selective estrogen receptor modulators (SERMs) bazedoxifene and lasofoxifene to bind and act on CB2 cannabinoid receptor. We have identified, for the first time, that CB2 is a novel target for bazedoxifene and lasofoxifene. Our results showed that bazedoxifene and lasofoxifene were able to compete for specific [3H]CP-55,940 binding to CB2 in a concentration-dependent manner. Our data also demonstrated that by acting on CB2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 20 publications
2
10
0
Order By: Relevance
“…17-β-Estradiol could be assumed to increase the expression of CB-2 receptors, as has been previously observed in osteoclasts in vitro (24), or it is possible that estrogens act through other, non-genomic mechanisms (26). Recent studies also show that selective estrogen modulators, raloxifene (27), bazedoxifene and lasofoxifene, behave as CB-2 inverse agonists (28), which may also be true for 17-β-estradiol and would correlate with the present results.…”
Section: Discussionsupporting
confidence: 86%
“…17-β-Estradiol could be assumed to increase the expression of CB-2 receptors, as has been previously observed in osteoclasts in vitro (24), or it is possible that estrogens act through other, non-genomic mechanisms (26). Recent studies also show that selective estrogen modulators, raloxifene (27), bazedoxifene and lasofoxifene, behave as CB-2 inverse agonists (28), which may also be true for 17-β-estradiol and would correlate with the present results.…”
Section: Discussionsupporting
confidence: 86%
“…For example, some studies have suggested that both crude cannabis extract and THC inhibit the binding of estradiol to estradiol receptors in vivo (74,75). Recent studies showed that some estrogen receptor modulators can bind to cannabinoid receptors (76,77). These results have raised the possibility that THC could regulate histone methylation through ER signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it should be noted that in this study, and as reported previously [17, 18], special assay conditions were needed to observe optimal CBR antagonism by SERMs. For example, assays were conducted at room temperature with a 30 min SERM pre-incubation period, followed by agonist exposure for 7 min.…”
Section: Discussionmentioning
confidence: 54%
“…However, due to the adverse effects of currently available drugs acting at CBRs, FDA approval of therapeutic cannabinoids unfortunately remains elusive. Recent studies by our group [16] and others [17, 18] have shown that several clinically available, FDA-approved drugs in the selective estrogen receptor modular (SERM) class (e.g. Z-Tamoxifen, Z-4-hydroxytamoxifen, and Raloxifen) also bind and modulate activity of CB1 and CB2Rs.…”
Section: Introductionmentioning
confidence: 99%